ToT Programme: Self-Value Excellence Programme by the Sarawak Chief's Minister Office - Amalia, Madihie (2016)
Presented to counsellors, members of Khidmat Sokongan Pekerja (KSP), and facilitators on Self-Value Excellence Module.